Are risk-based tax audit stretegies rewarded? An analysis of corporate tax avoidance - Eva Eberhartinger; Reyhaneh Safaei; Caren Sureth; Yuchen Wu (Arbeitskreis Quantitative Steuerlehre (arqus), 2021)
This study examines the relation between risk-based tax audit strategies and corporate tax avoidance. We exploit OECD data across 54 countries on risk profiling, predictive modeling, and internal intelligence functions in tax administrations from 2014 to 2017 to investigate whether risk-based tax audits have an incremental effect on tax avoidance beyond enforcement. Our results suggest that the use of risk-based tax audits is associated with lower tax avoidance when controlling for tax enforcement, firm-specific, and country-specific factors. Cross-sectional tests indicate that risk-based tax audit strategies are effective tools to curb tax avoidance across firms of all sizes. The results of additional cross-sectional analyses indicate that risk-based tax audits are more effective in countries with low governance quality, high GDP, and low trust in governments. In additional tests, we use country-level data on tax administration performance and find evidence that countries with a risk-based audit strategy have lower costs of tax enforcement and improve the performance of tax authorities. Overall, our findings indicate that risk-based tax audit strategies have an incremental effect on attenuating firms' tax avoidance and increasing tax revenue.
Keywords: H25; H26; M41; M42; M48; 330; tax audits; tax avoidance; tax compliance; tax enforcement; tax risk